The Experience of Factor Analysis of Conditions for Human Capital Formation and Development in Regions of Russian Federation - Zaborovskaya, Olga Vitalyevna; Plotnikova, Ekaterina Vasilyevna; Sharafanova, Elena Evgenyevna (International Journal of Economics and Financial Issues, 2015)
The article suggests a factor analysis procedure for assessment of conditions for human capital formation and development (CHCFD) in the Russian Federation for Russian environment. This assessment integrates 21 private index, which measures the deviation of the actual conditions for human capital formation and development in the RF and Federation constituent entities, from the best ones, achieved in any Russian region. Data base for calculations is the official statistics, presented in the period from 1999 to 2012. The factors are the irregularity coefficients of indices achievement, characterizing the conditions for human capital formation and development in the regions of the Russian Federation. The calculation results of influence of factors on the deviation of conditions for human capital formation and development in whole in Russian Federation are presented, and the analysis of territorial differences is carried out. There was determined the distribution of factor values, that influenced much on assessment of conditions for human capital formation and development, per Federal Districts (macroregions), different variation of factors was revealed. Intra-regional differences were analyzed based on distribution of factors that influenced much on the assessment of conditions for human capital formation and development, per the constituent entities of the Federation of the Northwestern Federal District. There were determined the regions, that had the most and the least favorable conditions from the positions of human capital. There was determined a possibility to collate the indices as per the share of influence on the assessment value, presenting the basis to determine the priorities in development of regional policy of human capital formation and development. Keywords: Human capital, Factors of development, Regional policy, Regional economy. JEL Classifications: J24; C31; H76; Z13